Convergence of growth rate of profitability in Maharatna and selected Navratna companies in India. (24th October 2022) - Singh, Krishna; Sur, Debasish
The present paper attempts to analyse the process of convergence of profitability measured in terms of return on capital employed in Maharatna and selected Navratna central public sector enterprises in India during the period 2002 to 2014. While analysing the absolute and conditional beta convergence as well as modified sigma convergence, fixed effect regression model was used. The net outcome derived from the analysis of the absolute and conditional beta convergence indicates a significant convergence with respect to the overall profitability in both the Maharatna and Navratna companies. The modified sigma convergence reflects that the differences in achievements of return on capital employed in different companies within the group stepped up over time. The study also reveals that the central public sector enterprises with lower initial earning capability grew faster as compared to the companies with higher initial overall profitability.